PENYELAMATAN DOKUMEN LIPI PASCABENCANA BANJIR TAHUN 2007 - Triyono, Triyono (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2009)
This article describe an experience of Centre for Scientific Documentation and Information (PDII LIPI) on handling their archives, documents, or books, toward flood disaster. Some methodes for example air drying, fan, vacuum drying and vacuum freeze dry chamber, has been used. A total of document consists of archives, books, has been restored through these avtivities. Fumigation is one of the process which should be done carefully, because there are many dangerous microorganism could attack those restrored documents.